Comparative analysis of brand management on social media: public universities and private universities in Ecuador - Alarcón López, Henry; Pazmiño Chancay, Rocío; Alarcón Chávez, Michelle (Scripta Mundi, 2024)
This article comparatively examines the brand management on social media of public and private universities in Ecuador, taking as case studies the University of Guayaquil and the Central University of Ecuador on the public universities side, and the Catholic University of Santiago de Guayaquil and the Pontifical Catholic University of Ecuador on the private side. The research is based on the analysis of publications made on Facebook, Instagram and TikTok during a period of six months, from January to June 2024. Key metrics such as the number of posts, interactions (likes, comments, shares) and the effectiveness of interaction with the audience are analyzed. The results allow observing notable differences between the communication strategies and the impact on brand management of the educational institutions studied.